General Control Non-derepressible 1 (AtGCN1) Is Important for Flowering Time, Plant Growth, Seed Development, and the Transcription/Translation of Specific Genes in Arabidopsis - Cui, Xiaona; Gao, Kaili; Wang, Linjuan; Lv, Mengyang; Li, Ziwen; Zheng, Donghua; Wu, Wenwu; Yao, Wen; Ding, Liying; Li, Xiao; Zhu, Jian-Kang; Zhang, Hairong (Frontiers in Plant Science, 2021)
We have previously demonstrated that General Control Nonderepressible 1 (AtGCN1) is essential for translation inhibition under cold stress through interacting with GCN2 to phosphorylate eukaryotic translation initiation factor 2 (eIF2). Here, we report that the flowering time of the atgcn1 mutant is later than that of the wild type (WT), which has a large number of mutants that cannot develop and produce viable seeds. The total and polysomal RNA sequencing results further show that the mutation of atgcn1 selectively alters the expression of genes at both transcriptional and translational levels. The classification of AtGCN1 target genes reveals AtGCN1 is involved in flower development, seed dormancy and seed development, response to osmotic stress, amino acid biosynthesis, photosynthesis, cell wall organization, protein transport and localization, lipid biosynthesis, transcription, macroautophagy, proteolysis and cell death. The results show that AtGCN1 is required for flowering time, plant growth, seed development and expression of selective genes in Arabidopsis.